2016
DOI: 10.2196/mhealth.6178
|View full text |Cite
|
Sign up to set email alerts
|

Formative Work to Develop a Tailored HIV Testing Smartphone App for Diverse, At-Risk, HIV-Negative Men Who Have Sex With Men: A Focus Group Study

Abstract: BackgroundAlthough gay, bisexual, and other men who have sex with men (MSM) are disproportionately affected by human immunodeficiency virus (HIV) infection, few test for HIV at regular intervals. Smartphone apps may be an ideal tool to increase regular testing among MSM. However, the success of apps to encourage regular testing among MSM will depend on how frequently the apps are downloaded, whether they continue to be used over months or years, and the degree to which such apps are tailored to the needs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 16 publications
4
63
0
Order By: Relevance
“…Overall, this study showed that Spanish-speaking MSM reported many of the same considerations (e.g., ease of use, perceived usefulness, security) that impacted their adoption and use of mobile apps and other technologies as shown in prior studies of primarily English-speaking MSM [11,15]. In addition, Spanish-speaking MSM noted that having a strong personal interest in the content of the mobile app strengthened their motivation to download the app on their phone.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Overall, this study showed that Spanish-speaking MSM reported many of the same considerations (e.g., ease of use, perceived usefulness, security) that impacted their adoption and use of mobile apps and other technologies as shown in prior studies of primarily English-speaking MSM [11,15]. In addition, Spanish-speaking MSM noted that having a strong personal interest in the content of the mobile app strengthened their motivation to download the app on their phone.…”
Section: Discussionsupporting
confidence: 66%
“…Smart phones, which include global positioning systems (GPS), short messaging services (SMS), and applications (apps) features, have become almost ubiquitous among Hispanic adults, including MSM as they tend to be early adopters of newer technologies [8]. Preliminary work, much of which is qualitative, has begun to understand how best to optimize content, design, and delivery features of mHealth technologies for HIV prevention and testing [9][10][11][12]. In the study by Goldenberg and colleagues, MSM preferred their HIV prevention app to: 1) have an educational component to guide their decisions for which test is best for them and prevention options; 2) be interactive and engaging with personalized feedback about their own sexual behaviors; 3) provide a social networking component with other MSM; 4) use language that is simple and understandable to the community; and 5) address privacy concerns by ensuring that the app is from a credible source and having secure messaging features [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations